ACCESS TO JUSTICE FOR PERSONS WITH DISABILITIES IN MALAWI: EXPLORING CHALLENGES AND POSSIBILITIES IN THE CRIMINAL JUSTICE SYSTEM (African Disability Rights Yearbook, 2021)
This paper interrogates the right of access to justice for persons with disabilities in Malawi. It begins by noting that, from a normative perspective, significant progress has been made in terms of securing the rights of persons with disabilities. This progress is reflected in Malawi’s ratification of the Convention on the Rights of Persons with Disabilities (CRPD) and the adoption of the Disability Act. The paper acknowledges that access to justice is a fundamental right for persons with disabilities since it can facilitate their enjoyment of other rights. After presenting the legal, institutional and policy framework that deals with persons with disabilities, the paper examines selected provisions in Malawi’s criminal procedure law and assesses their compatibility with the principles underlying the CRPD and the Disability Act. Amongst other things, the paper establishes that, the language employed by the criminal law is demeaning of persons with disabilities and that the procedures guiding criminal trials do not possess inbuilt avenues for facilitating reasonable accommodation. The paper recommends that an audit of all statutes in the criminal justice system be undertaken in order to inform legislative reforms or initiatives of reasonable accommodation. The paper also advocates for continuous disability-rights training for all actors in the criminal justice system and the domestication of the CRPD together with the ratification of its Optional Protocol.